Dual polarised aperture‐coupled patch antenna using asymmetrical feed. Issue 13 (1st October 2015) - Fang, Qingyuan; Song, Lizhong; Jin, Ming; Han, Yong; Qiao, Xiaolin
Abstract : Dual polarised antennas are normally fed by symmetrical feed networks in order to obtain symmetrical radiation patterns for two orthogonal polarisations. In this study, a dual polarised aperture‐coupled patch antenna using asymmetrical feed for X‐band application is proposed. The exploitation of asymmetrical feed structure in exciting dual polarisations turns out to be valid, and is capable of realising symmetrical radiation patterns just as the traditional feed networks have done. Besides, the asymmetrical feed provides a wide impedance bandwidth and high isolation between ports. Key parameters studies and current distributions analysis prove the feasibility of the asymmetrical feed. Both simulated and measured results indicate an impedance bandwidth over 35.2% and the isolation is higher than 30 dB over the entire bandwidth. The cross‐polarisation levels in the E‐ and H‐ planes for both polarisations are lower than −20 dB. Moreover, the antenna prototype shows good symmetrical property in radiation patterns for dual polarisations.